Pengaruh Pendidikan Karakter Islam Terhadap Kedisiplinan Siswa Sekolah Dasar - Deddy Yusuf Yudhyarta; Al Afif Hazmar; Iwan Agus Supriono; Taufik Helmi; Siti Patimah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Students who already have knowledge of Islamic character education should be able to apply discipline. But in reality there are still students who lack discipline. This study aims to find out how Islamic character education affects student discipline at the 010 Mumpa Public Elementary School, Tempuling district. The population in this study were 145 students with a sample of 59 people. Data collection techniques through questionnaires and interviews. Data analysis technique with a simple regression statistical test. The results of data analysis on the Influence of Islamic Character Education, at 84% on Student Discipline, at 87% obtained the results F count ≥ F table = 5.58 ≥ 4.02 then Ho is rejected means there is a positive and significant influence between Character Education on Student Discipline. While the results of the interviews show; (1) In general, character education is very good, (2). Student discipline is generally good, seen from students coming to school before the bell rings, neatly dressed (3). Islamic character education has an influence on student discipline. As students behave respectfully towards teachers, violations of discipline have begun to decrease. (4). The obstacles are students who have bad behavior which can sometimes affect other students, and the lack of attention from parents.